Association between coronary atherosclerotic burden and all-cause mortality among patients undergoing exercise versus pharmacologic stress-rest SPECT myocardial perfusion imaging. (October 2020) - Rozanski, Alan; Gransar, Heidi; Miller, Robert J.H.; Hayes, Sean W.; Friedman, John D.; Thomson, Louise E.J.; Berman, Daniel S.
Abstract: Background and aims: Patients with suspected coronary artery disease who undergo stress SPECT myocardial perfusion imaging (MPI) and require pharmacologic stress are at substantially increased mortality risk compared to those who can exercise. However, the mechanisms underlying this increased risk are not well delineated. To test whether increased atherosclerotic burden accounts for this increased risk, we assessed the association between coronary artery calcium (CAC) scores and mortality risk among patients undergoing exercise versus pharmacologic SPECT MPI. Methods: We assessed all-cause mortality in 2, 151 patients, followed for 12.2 ± 3.4 years, after undergoing stress-rest SPECT-MPI and CAC scanning within 3 months of each other. Patients were divided according to their mode of stress testing (exercise or pharmacologic). We further employed propensity analysis to create a subgroup of exercise and pharmacologic subgroups with comparable age, symptoms, and coronary risk factors. Results: Despite greater age and worse clinical profiles, pharmacologic and exercise patients had similar CAC scores. However, the hazard ratio (95% CI) for mortality was substantially greater among pharmacologic patients: 2.39 (1.83–3.10). For each level of CAC abnormality, pharmacologic patients had >2-fold increased risk adjusted hazard ratio for all-mortality risk ( p < 0.05 for each CAC level). Among propensity-matched exercise versus pharmacologic patients, the same findings were observed. Conclusions: Among patients referred for stress-rest SPECT-MPI and CAC scoring, pharmacologic patients have substantially increased mortality risk compared to exercise patients, despite having comparable levels of coronary atherosclerosis. Graphical abstract: Image 1 Highlights: Stress test patients requiring pharmacologic testing are at increased mortality risk. This risk persists among pharmacologic and exercise patients with similar clinical profiles. Nevertheless, atherosclerotic burden is similar among exercise and pharmacologic patients. Exercise patients with high CAC scores and pharmacologic patients with no CAC have similar risk. Prospective study is needed to delineate the drivers of mortality among pharmacologic patients.